STRATEGI KELANGSUNGAN HIDUP RUMAH TANGGA MISKIN DI PEDESAAN - Muntiyah Muntiyah; Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1997)
There are evidences that development in the last three decades has succeeded to lower the number of people living under poverty line. However, along with the economic recession this success may not continue, even it may be worsened. This study aims to understand survival strategies of the poor people in rural areas. There are at least four strategies done by the poor people. First of all, the poor people work longer to increase their income. Secondly, because of limited employment opportunity in rural areas, they commute to the city to involve in nonfarm activities. In addition, the poor people try to maximize the utilization of household member to get additional money for the householdor to lower expenditure. The last strategy is to find additional jobs as the mean to increase their income. Insome extends, there are stilla lot of poor people who can not afford all strategies mentioned above, since they have limited access for increasing their income.